Money Politics and Political Participation in the 2019 Legislative Elections in Banjar - Teguh Anggoro; Tina Cahya Mulyatin; Nova Chalimah Girsang; Riza Purnama; Tofan Ibrahim (UIN Sunan Gunung Djati, 2022)
The purpose of this study was to analyze the influence of money politics on people's political participation in the 2019 Legislative Election in Banjar, West Java. The results of this study are expected to provide strategic recommendations that can contribute directly to problem-solving for the KPU in Banjar City in making decisions, especially regarding money politics in Banjar. The method used in this research is a quantitative approach, data collection techniques with literature studies, and field studies with questionnaire instruments. The number of samples was 399 respondents who were part of the Permanent Voters List for the 2019 Banjar Legislative Election using the Proportionate Stratified Sampling technique. The data analysis technique in this research is to use the product moment analysis method. The results of the study show that the condition of money politics (Money Politic) carried out by unscrupulous candidates for the 2019 Banjar City DPRD legislative candidates found that 23% had been offered money or goods; Community political participation in the 2019 Legislative Election in Banjar City was highest based on sociological factors with a figure of 80.5%. The magnitude of the influence of Money Politic on political participation in the 2019 Legislative Election in Banjar City is 4.40%. The practice of money politics has no significant effect on public participation to actively participate in the 2019 Banjar City legislative election, the survey results explain an implementation that if there are legislative candidates who practice money politics to the public/voters, the money is received but does not guarantee that the public chooses the person. the legislative candidate.